(untitled) (Development Service Industry Management, 2024)
The article examines and analyzes recent research on the social responsibility of Ukrainian companies, identifying key trends and challenges they face. Based on the research, the main aspects to consider for developing effective corporate social responsibility strategies are highlighted. Social responsibility is defined as a key element of companies’ development strategy, involving the integration of social, economic, and environmental aspects into their goals. Main methods through which companies fulfill social responsibility include philanthropy, support for volunteering, implementation of ethical labor standards, and environmental conservation efforts. For instance, companies may monitor their environmental impact by focusing on reducing carbon emissions and waste. Additionally, there is social responsibility concerning ethical labor practices, which entails ensuring fair wages, especially where there are legal limitations on labor rights protection. Engaging in open dialogue with stakeholders and implementing socially beneficial initiatives contribute to the sustainable development and resilience of companies in the market. However, challenges such as insufficient awareness of the benefits of corporate social responsibility and the lack of adequate implementation tools require attention. This approach underscores the importance of engaging managerial personnel in implementing socially responsible business practices and convincing them of its positive impact on the overall success of the company. The integration of corporate social responsibility principles into business activities promotes their sustainable development, enhances their reputation, fosters investment attraction, and contributes to building a sustainable economic order in society. Survey results confirm the growing interest of Ukrainian companies in integrating social responsibility into their business strategies.